Copper oxide nanoparticles: from EU-regulatory landscape and mechanistic toxicity towards a cuproptosis-linked adverse outcome pathway - Sophie Scholz; Julia Prinz; Linde Sevenants; Andrea Holzwarth; Birgit Mertens; Robert Pieper; Vera Ritz; Kirsten Schulz; Holger Sieg; Aswin Mangerich; Linda Böhmert (Archives of Toxicology, 2026)
Copper is an essential trace element, yet concerns regarding its toxic potential have gained increasing attention, particularly with regard to nanoparticulate forms of copper oxides. Both CuO and Cu 2 O are currently authorised in the EU for use in agriculture, biocides, and animal nutrition, but regulatory clarity regarding their nanoforms remains limited. This comprehensive review—combining narrative, bibliometric, and systematic approaches—addressed three key questions: (i) whether CuO and Cu 2 O nanoparticles are sufficiently considered within EU regulations to prevent unintentional oral exposure via the food and feed chain, (ii) whether these nanoparticles can cross the intestinal barrier as intact particles and accumulate in tissues, and (iii) whether they elicit distinct biological responses, including regulated cell death pathways such as cuproptosis. With respect to question (i), a detailed analysis of EU legal frameworks revealed a heterogeneous regulatory landscape and a lack of binding provisions that would preclude unintended presence of copper oxide nanoforms in regulated materials. Although some nano-specific data requirements exist, empirical information on nanoparticulate fractions in commercial products is still lacking. With respect to questions (ii) and (iii), our systematic literature analysis supports consistent intracellular uptake of CuO and Cu 2 O nanoparticles, yet direct evidence for transport of intact particles across the intestinal barrier is scarce. Mechanistic evidence supports cuproptosis as a key pathway for CuO nanoparticle toxicity, while the extent to which these effects differ quantitatively from ionic copper remains unclear due to insufficient data using appropriate experimental controls. Notably, a pronounced data gap was identified for Cu 2 O nanoparticles across all evaluated domains. Finally, to organise and integrate the mechanistic evidence presented, we developed an adverse outcome pathway (AOP), registered as AOP 590 in the AOP Wiki, describing how increased intracellular copper can induce cuproptosis via disruption of energy metabolism. Collectively, these findings highlight the need for coordinated analytical, mechanistic, and regulatory research to support evidence-based risk assessment of CuO and Cu 2 O nanoparticles in the food and feed context.

Variability and uncertainty of data from genotoxicity test guidelines: what we know and why it matters - Giuseppa Raitano; Tessa E. Pronk; Chiara L. Battistelli; Cecilia Bossa; Vasiliki Hatzi; Dimitra Nikolopoulou; Evgenia Chaideftou; Olga Tcheremenskaia; Christelle Adam-Guillermin; Marc Audebert; Birgit Mertens; Martin Paparella (Archives of Toxicology, 2026)
This review comprehensively examines the variability and uncertainty associated with test guideline (TG)-conform genotoxicity data and explores the respective implications for the integration of non-animal-methods (NAMs) into regulatory frameworks. Historical amendments to OECD TGs are mapped to reveal the method’s evolution that improves the scientific quality of the data but also explains data heterogeneity within available databases. An analysis of the major genotoxicity databases ECVAM, ISSMIC, and OASIS demonstrates substantial variability in genotoxicity calls. Using the EFSA genotoxicity database, which currently harbours the best-curated (meta-) data, we estimate that 22–77% of compounds exhibit similarity of replicate results below 85%, depending on the assay. The potentially most important variables statistically explaining variability and sensitivity were analysed. The practical limitations to identify them with high reliability and to define their optimum needs to be accepted as a qualitative baseline uncertainty. These findings underscore the necessity of contextualizing NAM performance evaluations within the intrinsic variability and uncertainty of animal and in vitro reference data. We propose that this variability is explicitly considered in the development and validation of NAM-based Integrated Approaches for Testing and Assessment. This review provides a critical foundation for regulators and scientists aiming to enhance the acceptance and utility of NAMs in genotoxicity assessment.

In vitro to in vivo extrapolation modeling to facilitate the integration of transcriptomics data into genotoxicity assessment - Anouck Thienpont; Eunnara Cho; Andrew Williams; Matthew J. Meier; Carole L. Yauk; Marc A. Beal; Freddy Van Goethem; Vera Rogiers; Tamara Vanhaecke; Birgit Mertens (Toxicology, 2025)

Hazard characterization of the mycotoxins enniatins and beauvericin to identify data gaps and improve risk assessment for human health - Anne-Cathrin Behr; Christiane Kruse Fæste; Amaya Azqueta; Ana M. Tavares; Anastasia Spyropoulou; Anita Solhaug; Ann-Karin Olsen; Ariane Vettorazzi; Birgit Mertens; Bojana Zegura; Camille Streel; Dieynaba Ndiaye; et al. (Archives of Toxicology, 2025)
Enniatins (ENNs) and beauvericin (BEA) are cyclic hexadepsipeptide fungal metabolites which have demonstrated antibiotic, antimycotic, and insecticidal activities. The substantial toxic potentials of these mycotoxins are associated with their ionophoric molecular properties and relatively high lipophilicities. ENNs occur extensively in grain and grain-derived products and are considered a food safety issue by the European Food Safety Authority (EFSA). The tolerable daily intake and maximum levels for ENNs in humans and animals remain unestablished due to key toxicological and toxicokinetic data gaps, preventing full risk assessment. Aiming to find critical data gaps impeding hazard characterization and risk evaluation, this review presents a comprehensive summary of the existing information from in vitro and in vivo studies on toxicokinetic characteristics and cytotoxic, genotoxic, immunotoxic, endocrine, reproductive and developmental effects of the most prevalent ENN analogues (ENN A, A1, B, B1) and BEA. The missing information identified showed that additional studies on ENNs and BEA have to be performed before sufficient data for an in-depth hazard characterisation of these mycotoxins become available.

A benchmark concentration-based strategy for evaluating the combined effects of genotoxic compounds in TK6 cells - Julie Sanders; Roel Anthonissen; George E. Johnson; Tamara Vanhaecke; Birgit Mertens (Archives of Toxicology, 2025)

Author Correction: Hazard characterization of Alternaria toxins to identify data gaps and improve risk assessment for human health - Henriqueta Louro; Ariane Vettorazzi; Adela López de Cerain; Anastasia Spyropoulou; Anita Solhaug; Anne Straumfors; Anne-Cathrin Behr; Birgit Mertens; Bojana Žegura; Christiane Kruse Fæste; Dieynaba Ndiaye; Eliana Spilioti; et al. (Archives of Toxicology, 2024)

Assessment of receptor-mediated activity (AhR and ERα), mutagenicity, and teratogenicity of metal shredder wastes in Wallonia, Belgium - Besarta Matranxhi; Birgit Mertens; Roel Anthonissen; Jan Maes; Annelii Ny; Peter de Witte; Jean-Marc Brouhon; Benoit De Bast; Marc Elskens (Environmental Science and Pollution Research, 2024)

Hazard characterization of Alternaria toxins to identify data gaps and improve risk assessment for human health - Henriqueta Louro; Ariane Vettorazzi; Adela López de Cerain; Anastasia Spyropoulou; Anita Solhaug; Anne Straumfors; Anne-Cathrin Behr; Birgit Mertens; Bojana Žegura; Christiane Kruse Fæste; Dieynaba Ndiaye; Eliana Spilioti; et al. (Archives of Toxicology, 2024)
Fungi of the genus Alternaria are ubiquitous plant pathogens and saprophytes which are able to grow under varying temperature and moisture conditions as well as on a large range of substrates. A spectrum of structurally diverse secondary metabolites with toxic potential has been identified, but occurrence and relative proportion of the different metabolites in complex mixtures depend on strain, substrate, and growth conditions. This review compiles the available knowledge on hazard identification and characterization of Alternaria toxins. Alternariol (AOH), its monomethylether AME and the perylene quinones altertoxin I (ATX-I), ATX-II, ATX-III, alterperylenol (ALP), and stemphyltoxin III (STTX-III) showed in vitro genotoxic and mutagenic properties. Of all identified Alternaria toxins, the epoxide-bearing analogs ATX-II, ATX-III, and STTX-III show the highest cytotoxic, genotoxic, and mutagenic potential in vitro . Under hormone-sensitive conditions, AOH and AME act as moderate xenoestrogens, but in silico modeling predicts further Alternaria toxins as potential estrogenic factors. Recent studies indicate also an immunosuppressive role of AOH and ATX-II; however, no data are available for the majority of Alternaria toxins. Overall, hazard characterization of Alternaria toxins focused, so far, primarily on the commercially available dibenzo-α-pyrones AOH and AME and tenuazonic acid (TeA). Limited data sets are available for altersetin (ALS), altenuene (ALT), and tentoxin (TEN). The occurrence and toxicological relevance of perylene quinone-based Alternaria toxins still remain to be fully elucidated. We identified data gaps on hazard identification and characterization crucial to improve risk assessment of Alternaria mycotoxins for consumers and occupationally exposed workers.

Assessment of natural coagulants to remediate Tunisian textile wastewater by combining physicochemical, analytical, and toxicological data - Nosra Methneni; Roel Anthonissen; Jolien Van de Maele; Fatma Trifa; Luc Verschaeve; Hedi Ben Mansour; Birgit Mertens (Environmental Science and Pollution Research, 2020)

Dietary exposure of the Belgian population to mineral oil - Annelies Van Heyst; Séverine Goscinny; Sarah Bel; Stefanie Vandevijvere; Birgit Mertens; Marc Elskens; Els Van Hoeck (Food Additives & Contaminants: Part A, 2020)

Analysis of mineral oil in food: results of a Belgian market survey - Annelies Van Heyst; Mathias Vanlancker; Joeri Vercammen; Kathy Van den Houwe; Birgit Mertens; Marc Elskens; Els Van Hoeck (Food Additives & Contaminants: Part A, 2018)

A novel genotoxin-specific qPCR array based on the metabolically competent human HepaRG™ cell line as a rapid and reliable tool for improved in vitro hazard assessment - Gamze Ates; Birgit Mertens; Anja Heymans; Luc Verschaeve; Dimiter Milushev; Philippe Vanparys; Nancy H. C. Roosens; Sigrid C. J. De Keersmaecker; Vera Rogiers; Tatyana Y. Doktorova (Archives of Toxicology, 2018)

Safeguarding human health using in silico tools? - Melissa Van Bossuyt; Els Van Hoeck; Tamara Vanhaecke; Vera Rogiers; Birgit Mertens (Archives of Toxicology, 2017)

Mechanisms Linking Colorectal Cancer to the Consumption of (Processed) Red Meat: A Review - Daniel Demeyer; Birgit Mertens; Stefaan De Smet; Michèle Ulens (Critical Reviews in Food Science and Nutrition, 2016)

Distribution and phylogeny of hexachlorocyclohexane‐degrading bacteria in soils from Spain - William W. Mohn; Birgit Mertens; Josh D. Neufeld; Willy Verstraete; Victor De Lorenzo (Environmental Microbiology, 2006)
Summary Hexachlorocyclohexane (HCH)‐degrading bacteria are believed to mediate natural attenuation of HCH contamination and have potential for active bioremediation processes. This study addressed the very limited understanding of the distribution, diversity and substrate specificity of such bacteria from 13 soil samples, varying in levels of HCH contamination, from four sites in Spain. Hexachlorocyclohexane removal occurred in 16 of 36 enrichment cultures. Hexachlorocyclohexane‐degrading populations were clearly associated with HCH‐contaminated soils, and populations growing on the δ‐HCH isomer were only found in soil contaminated with δ‐HCH. β‐Hexachlorocyclohexane was persistent in enrichment cultures, and there was no evidence for populations growing on β‐HCH. From α‐ and γ‐HCH enrichment cultures, nine HCH‐degrading isolates were obtained, which were all Sphingomonas spp. Attempts to isolate organisms from δ‐HCH enrichment cultures failed. None of the isolates grew on HCH as a sole organic substrate in pure culture. All isolates degraded α‐ and γ‐HCH, and most degraded β‐HCH. δ‐Hexachlorocyclohexane inhibited growth of most isolates, but could be degraded by cell suspensions of at least four strains. Denaturing gradient gel electrophoresis indicated that the isolates represented predominant populations in the enrichment cultures, but additional predominant populations, including some Pseudomonas spp., could not be isolated.

Stereospecific effect of hexachlorocyclohexane on activity and structure of soil methanotrophic communities - Birgit Mertens; Nico Boon; Willy Verstraete (Environmental Microbiology, 2005)
Summary In the past decades, large amounts of non‐insecticidal hexachlorocyclohexane (HCH) isomers (α‐, β‐, δ‐ and ɛ‐HCH) have been dumped as side‐products of the insecticide γ‐HCH (lindane). This study investigates the effect of HCH isomers on methane oxidation, an important soil function performed by methanotrophic bacteria. Both activity and structure of the methanotrophic community were assessed, using methane oxidation assays and PCR‐DGGE (polymerase chain reaction‐denaturing gradient gel electrophoresis) respectively. Methane oxidation assays with historically polluted soils revealed that on the long‐term methane oxidation was inhibited by HCH pollution. PCR‐DGGE and diversity analysis based on Lorenz curves showed that the type I methanotrophic community was less evenly distributed in historically HCH‐polluted soils compared with less polluted reference soils. Short‐term experiments with methane‐enriched consortia further demonstrated that only γ‐ and δ‐isomers inhibited methane oxidation. Type I methanotrophs of methane‐enriched microbial consortia that received γ‐ or δ‐HCH evolved towards higher species richness. Apparently, for historically HCH‐polluted soils, a narrow community remained after long‐term exposure while in case of short‐term exposures, methane‐enriched consortia were converted into less active, but richer communities when they were stressed by the presence of γ‐ or δ‐HCH. This work demonstrates the importance of incorporating all isomers and possible other side‐products in risk assessment studies of persistent organic pollutants and the use of structural analysis of type I methanotrophic communities as evaluating tool.